Evaluation of a two dimensional analysis method as a screening and evaluation tool for anterior cruciate ligament injury - McLean, S. G.; Walker, K.; Ford, K. R.; Myer, G. D.; Hewett, T. E.; van den Bogert, A. J. (British Journal of Sports Medicine, 2005)
Background: Increased knee valgus predicts the risk of anterior cruciate ligament (ACL) injury, particularly in women. Reducing injury rates thus relies on detecting and continually evaluating people with relatively large valgus motions.